FEATURES OF ECOLOGICAL ETIQUETTE OF THE KYRGYZ PEOPLE (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
The article analyzes in detail the sensitive attitude of the Kyrgyz people to nature, living beings and the environment in general. And the author also says that if moral norms determine the content of actions and specify what people should do, then the culture of behavior shows how moral requirements can be specifically implemented in behavior, what their forms are, whether these forms are natural and organic and connected with a person and expressed that it had become the daily rule of his life. In addition, the article shows the actions of the Kyrgyz regarding taboos towards nature and animals. Taboo played a vital role in the daily life of the ancient Kyrgyz people. The article also reflects the attitude of nomadic Kyrgyz towards animals in everyday life, methods of slaughtering animals. The rules of etiquette for butchering an animal carcass in Kyrgyz culture are also given in detail.
Keywords: taboo, Kut, mazar, totem, etiquette, moral culture, butchering etc.